Chronic neutropenia: how best to assess severity and approach management?. Issue 10 (3rd October 2021) - Donadieu, Jean; Frenz, Stephanie; Merz, Lauren; Sicre De Fontbrune, Flore; Rotulo, Gioacchino Andrea; Beaupain, Blandine; Biosse-Duplan, Martin; Audrain, Marie; Croisille, Laure; Ancliff, Phil; Klein, Christoph; Bellanné-Chantelot, Christine
ABSTRACT: Introduction: Neutropenia is a relatively common finding in medical practice and the medical approach requires a gradual and pertinent diagnostic procedure as well as adapted management. Areas Covered: The area of chronic neutropenia remains fragmented between diverse diseases or situations. Here physicians involved in different aspects of chronic neutropenia gather both the data from medical literature till the end of May 2021 and their experience to offer a global approach for the diagnosis of chronic neutropenia as well as their medical care. Expert opinion: In most cases, the neutropenia is transient, frequently related to a viral infection, and not harmful. However, neutropenia can be chronic (i.e. >3 months) and related to a number of etiologies, some clinically benign, such as so-called 'ethnic' neutropenia. Autoimmune neutropenia is the common form in young children, whereas idiopathic/immune neutropenia is a frequent etiology in young females. Inherited neutropenia (or congenital neutropenia) is exceptional, with approximately 30 new cases per 10 6 births and 30 known subtypes. Such patients have a high risk of invasive bacterial infections, and oral infections. Supportive therapy, which is primarily based on daily administration of an antibiotic prophylaxis and/or treatment with granulocyte-colony stimulating factor (G-CSF), contributes to avoiding recurrent infections.